2021
DOI: 10.3390/jcm10091909
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Confirmatory Testing for SARS-CoV-2 Antibodies: Comparison of Health and Non-Health Workers in a Nationwide Healthcare Organization in Central Europe

Abstract: Despite being located close to the European epicenter of the COVID-19 pandemic in Italy, Austria has managed to control the first wave. In Austria, the largest health insurance fund covers 7 million people and has 12,000 employees, including 3700 healthcare workers (HCW). For patient and staff safety, transmission control measures were implemented and mass testing of employees for SARS-CoV-2 antibodies was conducted. An IgG SARS-CoV-2 rapid test on fingerstick blood was used as a screening test (ST), followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Factors associated with the high level of stress found among healthcare workers in four Latin American countries during the pandemic, including Chile, were working in intensive care and fear of infection or of infecting family members [ 48 ]. As might be expected, health professionals appear to have their mental health affected to a greater extent than other professionals [ 49 , 50 ], although the special preventive measures available to health professionals, compared to other workers, may compensate for their special risk of becoming infected, noting in Austria that the prevalence of the virus in health professionals was not higher than in the general population [ 51 ]. It has even been observed that healthcare professionals caring for COVID-19 patients may have also experienced positive changes in coping resources and job satisfaction in addition to adverse psychological effects [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Factors associated with the high level of stress found among healthcare workers in four Latin American countries during the pandemic, including Chile, were working in intensive care and fear of infection or of infecting family members [ 48 ]. As might be expected, health professionals appear to have their mental health affected to a greater extent than other professionals [ 49 , 50 ], although the special preventive measures available to health professionals, compared to other workers, may compensate for their special risk of becoming infected, noting in Austria that the prevalence of the virus in health professionals was not higher than in the general population [ 51 ]. It has even been observed that healthcare professionals caring for COVID-19 patients may have also experienced positive changes in coping resources and job satisfaction in addition to adverse psychological effects [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some confirm our results and some claim that HCWs had the same infection rate as the population during that time. [5][6][7][20][21][22][23][24][25][26][27][28][29][30][31][32][33] These discrepancies can be attributed to multiple reasons. The first reason is the type of test used to confirm infection; our study is slightly superior as it uses RT-PCR testing instead of serology testing.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were reported from hospitals in Ontario, Canada and Austria, who adopted rapid effective infection control measures. 24 , 36 Whereas partial use of PPE while working in departments with high patient load and turnover (emergency setting) is reported as a significant risk factor for infection. 22 , 37 The 2003 SARS outbreak at Prince of Wales Hospital is particularly edifying in this matter: the index case (the first case) was hospitalized but was not isolated for 15 days.…”
Section: Discussionmentioning
confidence: 99%